New Zealand Banks' Vulnerabilities and Capital Adequacy - Jang, B. (IMF Working Papers; Working Paper ;, 2013)
The paper finds that, given New Zealand's conservative approach in implementing the Basel II framework, New Zealand banks' headline capital ratios underestimate their capital strength. A comparison with Canadian, UK and Australian banks highlights the impact of New Zealand's more conservative approach. Stress tests in the paper show that four large New Zealand banks could withstand sizable stand-alone shocks to their exposure to either residential mortgages (calibrated on the Irish crisis experience) or corporate lending. However, combined shocks to both residential mortgages and corporate lending would put more pressure on the banks' capital. Given high bank concentration and large offshore wholesale funding needs, the merits of higher minimum capital requirements for systemically important domestic banks could be considered, together with other measures to be implemented.